2000
DOI: 10.1034/j.1399-6576.2000.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized surfactant in lung‐lavaged adult rats: factors influencing the therapeutic response

Abstract: Neither bolus nor aerosolized surfactant influenced lung morphology. Nebulized surfactant improved lung function but the effect was inferior to that obtained with bolus surfactant, and the outcome depended on the balance between the combined pool size of exogenous and endogenous surfactant and the vascular-to-alveolar leakage of serum protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The intubated preterm lamb model has been considered the gold standard model to study nRDS[23, 25, 27, 29], because the primary surfactant deficiency in the lambs adequately resembles human nRDS. The induction of lung injury by repeated BALs has also been used extensively as a model of acute lung-injury in the contest of RDS[12, 17, 18, 22, 44]. Nevertheless, the majority of these studies were performed during tracheal intubation and mechanical ventilation with full control of the airway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intubated preterm lamb model has been considered the gold standard model to study nRDS[23, 25, 27, 29], because the primary surfactant deficiency in the lambs adequately resembles human nRDS. The induction of lung injury by repeated BALs has also been used extensively as a model of acute lung-injury in the contest of RDS[12, 17, 18, 22, 44]. Nevertheless, the majority of these studies were performed during tracheal intubation and mechanical ventilation with full control of the airway.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the depletion of the intrapulmonary surfactant pools by repeated bronco-alveolar lavages (BALs) with saline solution has been frequently used in juvenile as well as in adult rats[17, 18], rabbits[19, 20], and pigs[21, 22], among others, to implement successful animal models of acute pulmonary failure in the context of RDS. On the other hand, the intubated premature lamb has been the gold standard animal model to study the pathogenesis and the treatments of nRDS for many decades.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported respiratory improvement with surfactant aerosol in animals with surfactant deficiency or dysfunction, 131,135,153,[155][156][157][158][159][160][161][162][163] although other aerosol studies have been less positive. [164][165][166][167] Several animal studies have directly compared aerosolization to tracheal instillation, and reported that aerosolization can have equal or greater effectiveness, 131,155,159 whereas others have found that instillation is more effective than aerosolization. 131,165,168 An example illustrating the need for further clarity on this issue is the study by Lewis et al 131 In lung-lavaged sheep, exogenous bovine lung extract surfactant was effective when instilled but ineffective when aerosolized, whereas beractant in the same animal model was more effective when aerosolized than when instilled.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
“…[164][165][166][167] Several animal studies have directly compared aerosolization to tracheal instillation, and reported that aerosolization can have equal or greater effectiveness, 131,155,159 whereas others have found that instillation is more effective than aerosolization. 131,165,168 An example illustrating the need for further clarity on this issue is the study by Lewis et al 131 In lung-lavaged sheep, exogenous bovine lung extract surfactant was effective when instilled but ineffective when aerosolized, whereas beractant in the same animal model was more effective when aerosolized than when instilled. Clinical studies with aerosolized surfactant have in general not had impressive results.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%
“…In these experiments we used the lavaged rat model because of its relative simplicity, stability and reproducibility [19,23,27]. Measures of gas exchange, pulmonary mechanics and capillary leak are all obtained in single experiments, and these are not possible in many newborn laboratory animals because of their small size.…”
Section: Discussionmentioning
confidence: 99%